Biblical Archaeology: The Hydra of Palestine’s History - Thompson, Thomas L. (Dansk Teologisk Tidsskrift, 2015)
Both Israel Finkelstein and William Dever have allegedly distanced themselves from the kind of “biblical archaeology” of William F. Albright. Their own efforts, however, to relate Palestinian archaeology and biblical narrative not only reflect Albright’s earlier methods, they create a politically oriented incoherence. In three recent works, since the turn of the millennia, Finkelstein uses archaeologically based arguments primarily to resolve problems of biblical interpretation. Dever, who also has published three biblical-archaeological studies since 2001, concentrates, rather, on archaeological issues, while using biblical narrative for his underlying historical context. A discussion of the figures of Solomon and Josiah on the one hand and a discussion of “landscape archaeology” and site classification, on the other hand, illustrate the shortcomings of their methodology.